Biotic material apparatus for thermally protecting and/or transporting temperature sensitive products - GERMAIN, Melissa; EMOND, Jean-pierre (2025)
Embodiments of the subject invention relate to a method and apparatus for shipping products so as to control the temperatures the products are exposed to. Embodiments can increase the amount of time the product and/or portions of the product experience a desired temperature range and/or reduce the amount of time the product and/or portions of the product experience temperatures outside 5 of the desired temperature range and/or experience an undesirable temperature range. Embodiments can incorporate biotic materials, such as wood fibers or moss, positioned around and/or near the product positioned inside a packaging container or around a pallet load, such that the biotic materials restrict heat flow from one or more locations on the exterior of the package to one or more other locations in the interior of the package. 10 Embodiments of the subject invention relate to a method and apparatus for shipping products so as to control the temperatures the products are exposed to. Embodiments can increase the amount of time the product and/or portions of the product experience a desired temperature range and/or 5 reduce the amount of time the product and/or portions of the product experience temperatures outside of the desired temperature range and/or experience an undesirable temperature range. Embodiments can incorporate biotic materials, such as wood fibers or moss, positioned around and/or near the product positioned inside a packaging container or around a pallet load, such that the biotic materials restrict heat flow from one or more locations on the exterior of the package to one or more other 10 locations in the interior of the package. ug u g m b o d i m e n t s o f t h e s u b j e c t i n v e n t i o n r e l a t e t o a m e t h o d a n d a p p a r a t u s f o r s h i p p i n g p r o d u c t s s o a s t o c o n t r o l t h e t e m p e r a t u r e s t h e p r o d u c t s a r e e x p o s e d t o m b o d i m e n t s c a n i n c r e a s e t h e a m o u n t o f t i m e t h e p r o d u c t a n d o r p o r t i o n s o f t h e p r o d u c t e x p e r i e n c e a d e s i r e d t e m p e r a t u r e r a n g e a n d o r r e d u c e t h e a m o u n t o f t i m e t h e p r o d u c t a n d o r p o r t i o n s o f t h e p r o d u c t e x p e r i e n c e t e m p e r a t u r e s o u t s i d e o f t h e d e s i r e d t e m p e r a t u r e r a n g e a n d o r e x p e r i e n c e a n u n d e s i r a b l e t e m p e r a t u r e r a n g e m b o d i m e n t s c a n i n c o r p o r a t e b i o t i c m a t e r i a l s , s u c h a s w o o d f i b e r s o r m o s s , p o s i t i o n e d a r o u n d a n d o r n e a r t h e p r o d u c t p o s i t i o n e d i n s i d e a p a c k a g i n g c o n t a i n e r o r a r o u n d a p a l l e t l o a d , s u c h t h a t t h e b i o t i c m a t e r i a l s r e s t r i c t h e a t f l o w f r o m o n e o r m o r e l o c a t i o n s o n t h e e x t e r i o r o f t h e p a c k a g e t o o n e o r m o r e o t h e r l o c a t i o n s i n t h e i n t e r i o r o f t h e p a c k a g e